2011
DOI: 10.1007/s11368-011-0454-0
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread endocrine activity in river sediments in Hesse, Germany, assessed by a combination of in vitro and in vivo bioassays

Abstract: Purpose There is a growing concern regarding the effects of endocrine disrupting compounds on humans and wildlife. Since some of them have the ability to bind to particulate matter, high concentrations can be reached in sediments of surface waters. The objective of this study was an assessment of 50 sediment samples from predominantly small rivers in the German federal state of Hesse with emphasis on endocrine activity. Materials and methods The freshwater mudsnail Potamopyrgus antipodarum was exposed to whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Galluba & Oehlmann [24] applied the in vivo reproduction test with P. antipodarum and the yeast estrogen screen (YES) as an in vitro assay in parallel for 50 sediments from smaller rivers and creeks. It was shown that 54% of the sediments exhibited a promoting effect on snail reproduction and also showed an estrogenic activity in the YES while 82% of the samples which were active in the YES caused an increased snail reproduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Galluba & Oehlmann [24] applied the in vivo reproduction test with P. antipodarum and the yeast estrogen screen (YES) as an in vitro assay in parallel for 50 sediments from smaller rivers and creeks. It was shown that 54% of the sediments exhibited a promoting effect on snail reproduction and also showed an estrogenic activity in the YES while 82% of the samples which were active in the YES caused an increased snail reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…Galluba & Oehlmann [24] also discussed the possibility that lower embryo numbers in the artificial control sediment may reflect sub-optimal conditions for the development and reproduction of the snails. However, if embryo numbers in the tested field sediments are not compared to the artificial control sediment but to a natural reference sediment with no measurable estrogenic activity in the YES, an identical number of sediments turned out to exhibit significantly more embryos.…”
Section: Resultsmentioning
confidence: 99%
“…2). Estrogenic activity has also been reported in sediments of other countries such as Korea (Koh et al 2006) and Germany (Galluba and Oehlmann 2011).…”
Section: Results and Discussion Eeq Measured By Yes Bioassaymentioning
confidence: 73%
“…EDCs, including natural chemicals and synthetic chemicals, have significant impacts on organisms even at a low dose (Froehner et al, 2012;Galluba and Oehlmann, 2012). In particular, estrogenic EDCs have high binding affinity to estrogen receptors and can act as estrogenic receptor (ER) agonists.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical analysis lacks the information of potential adverse effects to the organisms. In vivo and in vitro bioassays that can reflect the biological effects in complex environmental mixtures are used to study estrogenic activity (Jeffries et al, 2011;Galluba and Oehlmann, 2012). Especially, in vitro bioassays have been proved as a quite useful method to screen and quantify the estrogenic potency, due to its high sensitivity and low requirements to equipment (Svobodová et al, 2009;Kinani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%